Towards an Interactive and Participatory Risk Communication: Lessons Learned from COVID-19 in Indonesia - Gregoria A. Yudarwati; Ignatius A. Putranto; Ina N. Ratriyana; Philipus Parera (Cogent Social Sciences)
Using an experiential risk perception approach, this study examines public’s perceptions towards COVID-19 vaccination in Indonesia and proposes a model of risk communication that enables public’s participation and empowerment in risk management. This study involved those who have experienced COVID-19 vaccination in Indonesia. Based on an online survey, this study found that risk perception was not only about calculation based on scientific information but also about public experiences and beliefs. This study also found that health personnel was associated with scientific explanations about vaccine, while the government was associated with risk management governance. Following these findings, this study proposes a risk communication model that treats the public as a partner of the risk managing institutions. Incorporating the four functions of risk communication: [1] the enlightenment; [2] the trust-building; [3] the participative, and [4] the behavioural change, the model suggests interactive and participatory process involving an equal measure of listening and telling as well as a change from informing to partnering. Risk communication here is an empowering process through which the public can share what they think, how they feel, what they want and how they can achieve it to reduce the risks.